2021
DOI: 10.1021/acscatal.1c01847
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Mechanistic Investigations of Pd-Catalyzed Coupling/Cyclization and Cycloisomerization of Allenyl Malonates

Abstract: Pd-catalyzed transformations of allenyl malonates provide convenient access to functionalized carbocycles, but the influence of the ligand, solvent, base, and reaction conditions on the mechanism, regioselectivity, and product outcome of the cyclization is not well understood. Additionally, from the perspective of synthetic utility, access to either fully substituted or enantioenriched cyclopentane building blocks has not yet been achieved. This work describes how targeted changes to the reaction conditions en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Another stride in this direction was reported by Carreira and co-workers concerning an Ir-catalyzed enantioselective reductive deoxygenation of racemic tertiary allenyl alcohol (Scheme ). This transformation is rooted in the early examples of Pd- or Ir-catalyzed nucleophilic substitution reactions on allenyl alcohol derivatives, specifically an early example of Ir-catalyzed allenyl substitution of tertiary allenyl acetate using malonate as the nucleophile by Takeuchi and co-workers …”
Section: Introductionmentioning
confidence: 99%
“…Another stride in this direction was reported by Carreira and co-workers concerning an Ir-catalyzed enantioselective reductive deoxygenation of racemic tertiary allenyl alcohol (Scheme ). This transformation is rooted in the early examples of Pd- or Ir-catalyzed nucleophilic substitution reactions on allenyl alcohol derivatives, specifically an early example of Ir-catalyzed allenyl substitution of tertiary allenyl acetate using malonate as the nucleophile by Takeuchi and co-workers …”
Section: Introductionmentioning
confidence: 99%
“…For example, the Cazes group and Schomaker group reported the palladium-catalyzed coupling-cyclization of (2,3-butadienyl)malonate with organic halides to afford five-membered cyclopentene derivatives. 9 Ma and Oh groups observed that under the catalysis of Pd(PPh 3 ) 4 , the reaction of (2,3-butadienyl)malonate with organic halides formed a three-membered vinylic cyclopropane derivative with high selectivity. 10 The three-component tandem double addition cyclization of (2,3-butadienyl)malonate, organohalides and imines for the synthesis of polysubstituted cis -pyrrolidine derivatives was also achieved by the Ma group.…”
Section: Introductionmentioning
confidence: 99%